Morphological evidence for neuronal connections between the olfactory neurogenic region and the striatum in adult rats - Fabianová, Kamila; Martončíková, Marcela; Vanický, Ivo; Blaško, Juraj; Popovičová, Alexandra; Žideková, Monika; Račeková, Enikő (Frontiers in Neural Circuits, 2025)
The regulatory mechanisms of postnatal neurogenesis in the subventricular zone (SVZ) and the rostral migratory stream (RMS) are still not fully understood. Recent evidence suggests that neurogenesis in the SVZ/RMS may be regulated by neurons located directly in these regions. To date, two populations of neurons residing in the SVZ/RMS, which display the morphological characteristics of mature neurons, have been identified: nitric oxide (NO)-producing neurons and neurons expressing secretagogin (SCGN). The aim of our study was to map the possible projections of these neuronal populations in the SVZ/RMS. All experiments were performed on adult male Wistar albino rats. To test the hypothesis that nNOS- and SCGN-positive neurons of the SVZ and RMS send their axons to the striatum, we injected this target brain structure with the retrograde fluorescent tracer Fluoro-Gold (F-G). To verify the identity of nitrergic neurons and SCGN- expressing neurons, double immunofluorescent labeling with anti-nNOS/anti-SCGN and anti-F-G was performed. Microscopic analysis revealed the presence of F-G, administered into the striatum, in cells of the SVZ and different parts of the RMS. F-G-labeled cells in the SVZ/RMS were identified as either nitrergic neurons or SCGN-expressing neurons. Our results demonstrate a connection between mature neurons of the SVZ/RMS and the striatum.